The role of surface corrugation and tip oscillation in single-molecule manipulation with a non-contact atomic force microscope - Wagner, Christian; Fournier, Norman; Tautz, F. Stefan; Temirov, Ruslan (Beilstein Journal of Nanotechnology, 2014)
Scanning probe microscopy (SPM) plays an important role in the investigation of molecular adsorption. The possibility to probe the molecule–surface interaction while tuning its strength through SPM tip-induced single-molecule manipulation has particularly promising potential to yield new insights. We recently reported experiments, in which 3,4,9,10-perylene-tetracarboxylic-dianhydride (PTCDA) molecules were lifted with a qPlus-sensor and analyzed these experiments by using force-field simulations. Irrespective of the good agreement between the experiment and those simulations, systematic inconsistencies remained that we attribute to effects omitted from the initial model. Here we develop a more realistic simulation of single-molecule manipulation by non-contact AFM that includes the atomic surface corrugation, the tip elasticity, and the tip oscillation amplitude. In short, we simulate a full tip oscillation cycle at each step of the manipulation process and calculate the frequency shift by solving the equation of motion of the tip. The new model correctly reproduces previously unexplained key features of the experiment, and facilitates a better understanding of the mechanics of single-molecular junctions. Our simulations reveal that the surface corrugation adds a positive frequency shift to the measurement that generates an apparent repulsive force. Furthermore, we demonstrate that the scatter observed in the experimental data points is related to the sliding of the molecule across the surface.
Keywords: atomic force microscopy (AFM); force-field model; 3,4,9,10-perylene-tetracarboxylic-dianhydride (PTCDA); qPlus; single-molecule manipulation

(untitled) - Tautz, F. S. (Prog. Surf. Sci., 2007)

(untitled) - Otero, R.; Rosei, F.; Besenbacher, F. (Annu. Rev. Phys. Chem., 2006)

(untitled) - Temirov, R.; Lassise, A.; Anders, F. B.; Tautz, F. S. (Nanotechnology, 2008)

(untitled) - Lafferentz, L.; Ample, F.; Yu, H.; Hecht, S.; Joachim, C.; Grill, L. (Science, 2009)

(untitled) - Schull, G.; Frederiksen, T.; Arnau, A.; Sánchez-Portal, D.; Berndt, R. (Nat. Nanotechnol., 2010)

(untitled) - Fournier, N.; Wagner, C.; Weiss, C.; Temirov, R.; Tautz, F. S. (Phys. Rev. B, 2011)

(untitled) - Fu, Y.-S.; Schwöbel, J.; Hla, S.-W.; Dilullo, A.; Hoffmann, G.; Klyatskaya, S.; Ruben, M.; Wiesendanger, R. (Nano Lett., 2012)

(untitled) - Schulze, G.; Franke, K. J.; Pascual, J. I. (Phys. Rev. Lett., 2012)

(untitled) - Hauptmann, N.; Mohn, F.; Gross, L.; Meyer, G.; Frederiksen, T.; Berndt, R. (New J. Phys., 2012)

(untitled) - Chiutu, C.; Sweetman, A. M.; Lakin, A. J.; Stannard, A.; Jarvis, S.; Kantorovich, L.; Dunn, J. L.; Moriarty, P. (Phys. Rev. Lett., 2012)

(untitled) - Wagner, C.; Fournier, N.; Tautz, F. S.; Temirov, R. (Phys. Rev. Lett., 2012)

(untitled) - Pawlak, R.; Fremy, S.; Kawai, S.; Glatzel, T.; Fang, H.; Fendt, L.-A.; Diederich, F.; Meyer, E. (ACS Nano, 2012)

(untitled) - Mohn, F.; Gross, L.; Moll, N.; Meyer, G. (Nat. Nanotechnol., 2012)

(untitled) - Wegner, D.; Yamachika, R.; Zhang, X.; Wang, Y.; Crommie, M. F.; Lorente, N. (Nano Lett., 2013)

(untitled) - Langewisch, G.; Falter, J.; Fuchs, H.; Schirmeisen, A. (Phys. Rev. Lett., 2013)

(untitled) - Schuler, B.; Liu, W.; Tkatchenko, A.; Moll, N.; Meyer, G.; Mistry, A.; Fox, D.; Gross, L. (Phys. Rev. Lett., 2013)

(untitled) - de Oteyza, D. G.; Gorman, P.; Chen, Y.-C.; Wickenburg, S.; Riss, A.; Mowbray, D. J.; Etkin, G.; Pedramrazi, Z.; Tsai, H.-Z.; Rubio, A.; Crommie, M. F.; Fischer, F. R. (Science, 2013)

(untitled) - Albrecht, F.; Neu, M.; Quest, C.; Swart, I.; Repp, J. (J. Am. Chem. Soc., 2013)

(untitled) - Frei, M.; Aradhya, S. V.; Koentopp, M.; Hybertsen, M. S.; Venkataraman, L. (Nano Lett., 2011)

(untitled) - Aradhya, S. V.; Frei, M.; Hybertsen, M. S.; Venkataraman, L. (Nat. Mater., 2012)

(untitled) - Hao, X.; Zhu, N.; Gschneidtner, T.; Jonsson, E. Ö.; Zhang, J.; Moth-Poulsen, K.; Wang, H.; Thygesen, K. S.; Jacobsen, K. W.; Ulstrup, J.; Chi, Q. (Nat. Commun., 2013)

(untitled) - Aradhya, S. V.; Venkataraman, L. (Nat. Nanotechnol., 2013)

(untitled) - Toher, C.; Temirov, R.; Greuling, A.; Pump, F.; Kaczmarski, M.; Cuniberti, G.; Rohlfing, M.; Tautz, F. S. (Phys. Rev. B, 2011)

(untitled) - Wagner, C.; Fournier, N.; Ruiz, V. G.; Li, C.; Müllen, K.; Rohlfing, M.; Tkatchenko, A.; Temirov, R.; Tautz, F. S. (2014)
to be published

(untitled) - Rohlfing, M.; Bredow, T. (Phys. Rev. Lett., 2008)

(untitled) - Rubio, G.; Agraït, N.; Vieira, S. (Phys. Rev. Lett., 1996)